Third generation environmental rights related to environmental decisionmaking and genetically modified organisms for sustainable development - Ansari, Abdul Haseeb; Al-Gasim, Saa Abu (AENSI Publications, 2014)
Third generation environmental rights have developed out of the loggerhead situation of the promotion of development and trade, including international trade, and conservation of the environment. It was first realised at the UN Conference on Human Environment 1972 that unfettered developmental might adversely affect the environment and can thus cause deleterious impact on its quality, which, in effect, may be detrimental to the humanity. It gave rise to the idea of sustainable development, which encompassed all human activities and dictates them to be environmentally responsible. It has to be judged on the basis of Impact Assessment. Third generation environmental rights together strive to save the world from the ultimate disaster. Right to access to information, right participate in environmental decision-making, access to justice, right to get precautionary principle applied to genetically modified organisms (GMOs) and right to information with respect to GM food are crucial environmental rights among them. The paper discusses them, except access to justice, and offers certain suggestions for ensuring these rights to the benefit of all.